Building a Static Farm Level Spatial Microsimulation Model: Statistically Matching the Irish National Farm Survey to the Irish Census of Agriculture - Stephen Hynes; Karyn Morrissey; Cathal O'donoghue (European Regional Science Association (ERSA), 2006)
This paper looks at the statistical matching technique used to match the Irish Census of Agriculture to the Irish National Farm Survey (NFS) to produce a farm level static spatial microsimulation model of Irish agriculture. The match produces a spatially disaggregated population microdata set of farm households for all of Ireland. Using statistical matching techniques, economists can now create more attribute rich datasets by matching across the common variables in two or more datasets. Static spatial microsimulation then uses these synthetic datasets to analyse the relationships among regions and localities and to project the spatial implications of economic development and policy changes in rural areas. The Irish agriculture microsimulation model uses one of many combinational optimatisation techniques - simulated annealing - to match the Census of Agriculture and the NFS. The static model uses this matched NFS and Census information to produce small area (District Electric Divisions (DED)) population microdata estimates for a particular year. Using the matched NFS/Census microdata, this paper will then analysis the regional farm income distribution for Ireland.
Keywords: 330